Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 04, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 04, 1930. In 1879, the legislature convened in January for the first session to be held in the new capitol, the structure which has been in use ever since. January sessions began in 1877. Theretofore the general assembly convened in May. Hawley's friends had gotten up a circular discussing him in connection with the senatorship which was distributed among the members of the legislature without the general's knowledge. Editorially the Courant said it would be "false modesty to ignore the fact that General Hawley was the first choice of a majority of republicans for senator." One argument used against Hawley was that if he were elected senator the First district congress seat might be lost to the republicans. There also were suggestions that he should wait until the next year before seeking promotion to the upper house. However, the Hawley men had their answer to all this and were not deterred.
1 electronic record. Scanned newspaper article. 1 image scans. 871 KB (892,447 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 19.0 MB (19,982,142 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers